2022
DOI: 10.3390/ijms23052525
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline Extracted from Fu Brick Tea Affects the Metabolism of Preadipocytes and Body Fat in Mice as a Pancreatic Lipase Inhibitor

Abstract: The dramatic increase in obesity is putting people under increasing pressure. Lipase inhibitors, as a kind of effective anti-obesity drug, have attracted more and more researchers’ attention in recent years because of their advantages of acting on the intestinal tract and having no side effects on the central nervous system. In this study, lipase inhibitor Fu Brick Theophylline (FBT) was screened based on enzyme molecular dynamics, and the inhibition mechanism of lipase inhibitors on obesity was analyzed and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…43 Another study showed that theophylline extracted from Fu brick tea increased the secretion of FAHFAs in high-fat-diet fed nutritionally obese mice, which further contributed to the levels of total cholesterol and triglycerides. 44 A later study reported that naringenin could affect the serum metabolism of FAHFAs to prevent nonalcoholic fatty liver disease in NASH-inducing methionine–choline-deficient diet mice. Moreover, metabolic homeostasis in azithromycin-induced disordered intestinal microecology mice could be improved by the supplementation of alginate oligosaccharide, which was via the Bacteroides acidifaciens – FAHFAs axis.…”
Section: Discussionmentioning
confidence: 99%
“…43 Another study showed that theophylline extracted from Fu brick tea increased the secretion of FAHFAs in high-fat-diet fed nutritionally obese mice, which further contributed to the levels of total cholesterol and triglycerides. 44 A later study reported that naringenin could affect the serum metabolism of FAHFAs to prevent nonalcoholic fatty liver disease in NASH-inducing methionine–choline-deficient diet mice. Moreover, metabolic homeostasis in azithromycin-induced disordered intestinal microecology mice could be improved by the supplementation of alginate oligosaccharide, which was via the Bacteroides acidifaciens – FAHFAs axis.…”
Section: Discussionmentioning
confidence: 99%
“…The impaired clearance of chylomicrons, LDL, very-low-density lipoprotein (VLDL) and other substances in the plasma of ApoE –/– mice leads to the deposition of a large number of lipid substances in the liver. ApoE –/– mice can better simulate the occurrence and development of human NAFLD, and are a reliable model for the study of NAFLD ( 12 , 13 ). In this study, the body weight, liver weight, abdominal fat weight, and ALT and AST activities of the FBT groups were lower than those of the model group, which reflected that FBT played a protective role for the liver.…”
Section: Discussionmentioning
confidence: 99%
“…During the fermentation process of FBT, some new are substances formed, such as theaflavin, thearubin, and theabrownin (10). Previous studies have shown that FBT and its extract can reduce blood lipids and oxidative stress in high-fat fed mice, improve lipid metabolism (11)(12)(13), and reduce obesity by regulating the gut microbiota (14,15). However, whether FBT can alleviate NAFLD injury through the gut microbiota has not been reported.…”
mentioning
confidence: 99%
“…During the flowering period, with the growth and reproduction of the dominant strain Eurotium cristatum , a series of complex changes have taken place in the biochemical components of FBT, thus forming the unique aroma and taste. Recently, FBT has attracted much attention due to its unique effects of promoting health, such as immune regulation (Sun et al., 2022 ; Xie et al., 2020 ), antioxidation (Song & Gao, 2014 ; Zhao et al., 2022 ), antiobesity (Li et al., 2022 ; Li, Liu, et al., 2013 ; Liu et al., 2015 ), anti‐diabetes, blood lipid lowering (Li, Lo, et al., 2013 ; Liu et al., 2020 ; Liu, Liu, et al., 2022 ), regulation of intestinal flora (Li et al., 2022 ; Zhang, Ren, Zhao, Cheng, et al., 2022 ), liver protection (Foster et al., 2016 ), antiproliferation (Luo et al., 2013 ; Tian et al., 2016 ), and antibacterial (Keller et al., 2013 ; Wang et al., 2015 ). FBT has become a common drink in daily life.…”
Section: Introductionmentioning
confidence: 99%